A mononuclear cobalt complex for water oxidation: new controversies and puzzles. Issue 46 (14th November 2018) - Safdari, Rasoul; Mohammadi, Mohammad Reza; Hołyńska, Małgorzata; Chernev, Petko; Dau, Holger; Najafpour, Mohammad Mahdi
Abstract : Herein the role of a mononuclear cobalt(iii ) complex, [Co III (DPKOH)2 ]ClO4 (DPK = di(2-pyridyl)ketone), in the water electrooxidation process is reinvestigated. Abstract : Herein the role of a mononuclear cobalt(iii ) complex, [Co III (DPKOH)2 ]ClO4 (DPK = di(2-pyridyl)ketone), in the water electrooxidation process is investigated with scanning electron microscopy, energy dispersive spectrometry, X-ray diffraction studies, NMR, chronoamperometry, cyclic voltammetry, extended X-ray absorption fine structure and X-ray absorption near edge structure determination. Our experiments show that, in comparison to the reported literature, other cobalt-containing structures on the surface of the FTO electrode could also be the true catalyst for water oxidation.